Towards a Methodology for the Translation of Japanese Patent Claims - Matthew, Robert (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractThe object of this current research is a study of Japanese patents and in particular a study of patent claims. Attention is focussed on their vocabulary and style and especially on their syntactic structure. Here regularities are sought with the intention of subjecting them to a systematic explanation. It is hoped that this explanation will facilitate 1) an understanding of their structure 2) their translation into English and 3) eventually a possible numerical encoding system that may be of assistance in mechanical translation with a minimum of postediting.